Structural correlates of lifetime voice-hearing in patients with borderline personality disorder: a pilot study - Kubera, Katharina Maria; Schmitgen, Mike; Hildebrandt, Viviane; Neukel, Corinne; Otte, Marie-Luise; Sicorello, Maurizio; Steinmann, Sylvia; Herpertz, Sabine; Wolf, Robert Christian (Neuropsychobiology, 2023)
Introduction: Auditory verbal hallucinations (AVH) are transdiagnostic phenomena that can occur in several mental disorders, including borderline personality disorder (BPD). Despite the transdiagnostic relevance of these symptoms, very little is known about neural signatures of AVH in BPD. Methods: We used structural magnetic resonance imaging to investigate multiple markers of brain morphology in BPD patients presenting with a lifetime history of AVH (AVH, n = 6) versus BPD patients without AVH (nAVH, n = 10) and healthy controls (HC, n = 12). The Computational Anatomy Toolbox (CAT12) was used for surface-based morphometric analyses that considered cortical thickness (CTh), gyrification (CG), and complexity of cortical folding (CCF). Factorial models were used to explore differences between AVH patients and HC, as well as between the patient groups. Results: Compared to HC, AVH patients showed distinct abnormalities in key regions of the language network, i.e., aberrant CTh and CG in right superior temporal gyrus and abnormal CCF in left inferior frontal gyrus. Further abnormalities were found in right prefrontal cortex (CTh) and left orbitofrontal cortex (CCF). Compared to nAVH patients, individuals with AVH showed abnormal CTh in right prefrontal cortex, along with CCF differences in right transverse temporal, superior parietal, and parahippocampal gyri. CG differences between the patient groups were found in left orbitofrontal cortex. Conclusion: The data suggest a transdiagnostic neural signature of voice-hearing that converges on key regions involved in speech generation and perception, memory and executive control. It is possible that cortical features of distinct evolutionary and genetic origin, i.e., CTh and CG/CCF, differently contribute to AVH vulnerability in BPD.